Towards an eco-literate tertiary music education: Notes from a South African context. (February 2022) - Jorritsma, Marie
On 20 September 2019 in Cape Town, as part of the global protests on inaction on climate change, the African Climate Alliance submitted a memorandum of demands to South African government representatives, one of which was 'the creation of a mandatory climate-education curriculum for South Africa'. This raises the question of how this imperative would be met within a tertiary music education context. Does the justified insistence on decolonised curricula in the period following the national #FeesMustFall protests of 2015–2016 allow space for inclusion of climate education? Given the links between social justice and environmental justice, there is certainly an argument for a focus on eco-literate education. What, then, would this include at South African tertiary music level? There are several (mostly United States based) course syllabi available online which focus mainly on themes and case studies in the field of ecomusicology. Daniel J. Shevock's work on eco-literate music pedagogy strongly advocates for a place-based approach, but Greg Garrard's critique would indicate otherwise. This article examines eco-critical and eco-literate theories and their application to music and uses the author's own teaching context to outline ideas for integrating a more climate-related educational approach.